Tissue-engineered human articular cartilage demonstrates intense immunopositivity for collagen type II - Sha'ban, Munirah; Saim, Aminuddin; Chua, Kien Hui; Osman Cassim, Samsudin; M. Yusuf, Badrul Akmal Hisham; Baharudin, Azmi; Hussien, Fuzina Nor; Idrus, Ruszymah (Penerbit Universiti Sains Malaysia, 2006)
Tissue engineering is known as an interdisciplinary biomedical field that applies the principles and method of engineering and life sciences toward the development of biological substitutes that restore, maintain, or improve tissue function. Our laboratory has successfully cultured human articular chondrocytes and formed tissue-engineered cartilage, which is reliable for replacement of damaged tissue. Yet, we still need to analyse whether the tissue-engineered cartilage has similarity to the native cartilage. This study was designed to evaluate the quality of human articular cartilage using immunohistochemistry (IHC) technique. Human articular cartilages were obtained from excessive tissues from consented patients after joint surgery. Chondrocytes were isolated from tissue via enzymatic digestion and cultured in growth media for several passages to obtain sufficient cells. The cells were then transformed into three-dimensional in vitro constructs using biodegradable scaffold and were placed subcutaneously in the nude mice. Constructs were harvested after 8 weeks and were analysed by IHC technique to detect the presence of collagen type I, collagen type II and fibrocytes surface protein. The results showed that stable in vitro construct mature into tissue-engineered cartilage after implantation, which grossly resembled native cartilage. In vitro construct strongly expressed collagen type I, collagen type II and the fibrocytes surface protein at the pericellular. In vivo construct showed the distribution of collagen type II expression throughout the tissue, which denotes good quality hyaline cartilage. In conclusion, we have successfully engineered human articular cartilage which resembles the native tissue by IHC evaluation technique.